Study on Dispersion of Cement Grout in Sand considering Filtration Effect through the EDTA Titration Test. (31st December 2020) - Li, Daimao; Li, Xuhui; Hu, Yu; Zhang, Sizhan; Mei, Chao; Wu, Hao; Sun, Xiaohui; Fu, Yanbin
Abstract : When grouting in a sand layer, the filtration of the layer on cement particles is an important aspect affecting the grout dispersion. However, few laboratory studies have been conducted to investigate the distribution of cement particles along the direction of dispersion. In this study, a group of laboratory tests were conducted by grouting in a sand layer under different levels of pressure. The distributions of cement particles in sand after curing were then measured using the EDTA titration test. The results show that, due to the filtration effect, the cement content along the radial direction of dispersion decreases nonlinearly in a reversed S shape. The filtration effect becomes more obvious when grouting with a higher grout concentration. With the decrease in grout concentration, the filtration effect becomes weak and cement particles could disperse farther in the sand layer, but the cement content in a farther location becomes lower and the improvement of the soil strength is limited. In the end, the measured results were compared with the calculated results according to an existing theoretical study and the trend reasonably matches with each other.